ESTABLISHMENT OF NOVEL URINARY KIDNEY DISEASE NEW BIOMARKERS AND THERAPEUTIC EFFECT OF METHANOL FRACTION OF TERMINALIA ARJUNA ON ACETAMINOPHEN INDUCED KIDNEY DISEASE IN RATS - GIRI, DEBLINA; DAS, KOUSHIK; KUMAR NANDI, DILIP (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: There were main two objectives, first was the identification of best biomarkers for early screening of kidney diseases whether plasma urea and creatinine or novel urinary low molecular weight protein biomarkers Interleukin-18 (IL-18), kidney injury molecule-1 (KIM-1), and cystatin-C. Second was the therapeutic efficacy of methanol fraction of Terminalia arjuna (MFTA) on urinary novel biomarkers. Methods: A total of 35 adult male rats were divided into three Groups (n=5), Group 1 was fed normal food, Group 2, normal food with administration of acetaminophen (APAP) for 5 days, 10 days, and 15 days, and Group 3, normal food with administration of APAP and coadministration of MFTA for 5 days, 10 days, and 15 days. All rats were sacrificed at 15th day of the experiment. Results: Results showed 5 days, 10 days, and 15 days administrations of APAP increased novel urinary biomarkers as IL-18, KIM-1 near two-folds and cystatin-C near six-folds increased than old biomarkers plasma urea and plasma creatinine. Administration of APAP with coadministration of MFTA represented the protective effect by decreasing old and new novel biomarkers with superoxide dismutase and catalase but malondialdehyde level increased. Sodium dodecyle sulphate-polyacrylamide gel electrophoresis showed new low molecular weight urinary protein bands in APAP administration rats, the protective effect of MFTA presents no band at this molecular level as normal rats. Conclusion: MFTA is the most potent nephroprotective agent, and urinary low molecular proteins are the best thing diagnostic tools for early detection of kidney disease over common plasma urea and creatinine.